Family existence to prepare a generation of Islamic Quality in the Millennial era - Fitriana, Fitriana; Supian Ramli; Anwar Sanusi; Suhertina (ADPISI (Asosiasi Dosen Pendidikan Agama Islam Se-Indonesia), 2024)
In the current global era, there are many opportunities and challenges to make Indonesia develop, especially for generations that have an impact on society, nation, and state. A nation will become prosperous and advanced depending on the condition of the generation, which acts as an agent of change, and in 2045 it is hoped that Indonesia will be golden. This research aims to elaborate on the theory and existence of the family, including 1) the meaning of a quality generation, 2) factors that influence a quality generation, and 3) the existence of the family in preparing an Islamic quality generation. The existence of the family in preparing a quality generation is the main foundation using the library research method, with data collection in the form of documentation. The results of the research are that the Islamic quality generation can be seen from the quality of faith, intellectuals, pious deeds, and social qualities. A quality generation that is not only good in its vertical relationship with God (hablumminallah), but also horizontally with humans (hablimminannas). The existence of the family in preparing a generation of Islamic quality by paying attention to Bihifzi anwalihim (family that protects wealth, Bihusni tarbiyatihim (preparing good education), and Wa taf adza adhum (resist disease. Apart from that, from a physical, psychological, spiritual, social, and cultural perspective.